Unusual behaviour of triphenylstibine complexes of zerovalent platinum - Barbiéri, Roberto S. [UNESP]; Klein, Stanlei I. [UNESP]; Massabni, Antonio C. [UNESP] (Royal Society of Chemistry (RSC), 1987)
The novel triphenylstibine complexes PtL2, PtL3, and (PtL3)nN2 (L = SbPh3) have been synthesised; the binary compounds are unusually unreactive even towards cold mineral acids.